Probabilities of wet spells over North Eastern India leading to flood condition
Hkkjh o"kkZ ds dkj.k Åijh tyxzg.k ks=ksa ls uhps dh vksj cgus okys ty ds vR;kf/kd rst izokgksa dks lekfgr djus ds fy, ufn;ksa ds rVksa ds vanj dh rjQ vi;kZIr LFkku gksus ds dkj.k ck<+ vkrh gSA vle vkSj es?kky; ds mi[kaMksa vkSj Hkkjr ds mRrjh iwohZ Hkkxksa ds mifgeky; if’pe caxky ds ks= nfk.k if’peh ekWulwu _rq ds le; ck<+ ls xzLr jgrs gSaA bl v/;;u esa vle vkSj es?kky; ds mi[kaMksa rFkk mifgeky; ds if’peh caxky ds dqN pqfuank ftyksa esa yxkrkj o"kkZ okys 2 vkSj 3 lIrkgksa ds lqfuf’pr Fkzs’kksYM eku ds vk/kkj ij igys Øe ds ekdksZo psu ekWMy kjk vkdfyr fd, x, laHkkoukvksa dks crkus dk iz;kl fd;k x;k gSA dqNsd fo’ks"k ks=ksa ds fy, Hkkjh o"kkZ dh laHkkouk okyh vof/k;ksa dk irk yxk;k x;k gS tc o"kkZ dk ckSNkjksa dh laHkkouk,¡ 80 izfr’kr ls vf/kd gksus ij mu ks=ks esa Hkkjh o"kkZ dh psrkouh vkSj muls fuiVus dh ;kstuk cukbZ tk ldrh gSA Floods are caused by the inadequate capacity within the banks of rivers to contain the high flows brought down from the upper catchments due to heavy rainfall. The sub-divisions Assam and Meghalaya and Sub-Himalayan West Bengal from northeastern parts of India are prone to flood conditions in the southwest monsoon season. In the present study an attempt has been made to give the probabilities computed by first order Markov chain model with certain threshold value for 2 and 3 consecutive wet weeks for selected districts of the sub-divisions Assam and Meghalaya and Sub-Himalayan West Bengal. The critical periods identified for certain region when probabilities of wet spells exceed 80% may lead to give awareness and planning for heavy rainfall in those areas. , number=3, journal=MAUSAM, author=GORE , P.G. and CHAVAN, A.B., year=2013, month=Jul., pages=475–480